An Optical Sensor Based on a Photonic Polymer Film to Detect Calcium in Serum. (7th January 2016) - Moirangthem, Monali; Arts, Remco; Merkx, Maarten; Schenning, Albertus P. H. J.
Abstract : An optical calcium sensor is fabricated based on a cholesteric liquid crystalline (CLC) polymer containing benzoic acid metal binding sites. A chiral imprinted CLC polymer is made which is subsequently treated with KOH to yield a responsive green reflecting film. On investigation of various metal ions, the polymer film shows a high optical response, and selectivity for calcium ions, which is related to the preorganized binding sites in the ordered liquid crystalline phase, leading to a blue reflecting film. The photonic polymer film is sensitive to Ca 2+ within the physiologically relevant concentration range of 10 −4 to 10 −2 m . Measurement of total calcium concentration in serum is also investigated using the film. The optical responses of normal serum and samples mimicking hypocalcemia and hypercalcemia can be clearly distinguished, providing a cheap, battery‐free, and easy‐to‐use alternative for calcium determination in clinical diagnostics. Abstract : Detection of calcium ions in aqueous solutions is realized by an optical sensor based on a cholesteric liquid crystalline polymer. It shows a color change from green to blue discernable by the naked eye. A proof of principle for the viability of this calcium sensor in the field of clinical diagnostics is also presented.